European guidelines (S1) on the use of high-dose intravenous immunoglobulin in dermatology - Enk, Alexander; Hadaschik, Eva; Eming, R.; Fierlbeck, G.; French, L. E.; Girolomoni, G.; Hertl, M.; Jolles, S.; Karpati, S.; Steinbrink, K.; Stingl, G.; Volc‐Platzer, B.; et al. (Journal of the European Academy of Dermatology and Venereology, 2016)
Background The treatment of severe dermatological autoimmune diseases and toxic epidermal necrolysis (TEN) with high-dose intravenous immunoglobulin (IVIg) is a well-established procedure in dermatology. As treatment with IVIg is usually considered for rare clinical entities or severe clinical cases, the use of immunoglobulin is not generally based on data from randomized controlled trials that are usually required for the practice of evidence-based medicine. Owing to the rarity of the indications for the use of IVIg, it is also unlikely that such studies will be available in the foreseeable future. Because the high costs of IVIg treatment also limit its first-line use, the first clinical guidelines on its use in dermatological conditions were established in 2008 and renewed in 2011. Materials and methods The European guidelines presented here were prepared by a panel of experts nominated by the EDF and the EADV. The guidelines were developed to update the indications for treatment currently considered as effective and to summarize the evidence base for the use of IVIg in dermatological autoimmune diseases and TEN. Results and conclusion The current guidelines represent consensual expert opinions and definitions on the use of IVIg reflecting current published evidence and are intended to serve as a decision-making tool for the use of IVIg in dermatological diseases.
Gesehen am 08.05.2020